Desenvolvimento das formulações de hidrogel à base de colágeno extraído da pele de tilápia (Oreochromis niloticus) - Gomes, Joyce de Pontes (2021)
The aging process provides greater fragility to the skin and the appearance of wounds. Lower limb venous hypertension and diabetes, which are common pathologies in the elderly people, can cause chronic wounds that are difficult to treat and have a higher risk of infections. Hydrogels are widely used in the treatment of these wounds; however, most hydrogels available on the market do not contain a healing active ingredient, working as an agent to promote a faster healing. Tilapia skin, according to studies for treatment of burns, was able to accelerate the healing process, which increased researchers' interest in knowing which agent causes this effect. Therefore, the purpose of this work was the development of a healing product, whose active principle is tilapia skin collagen with potential healing activity. Therefore, the extraction of collagen from the tilapia skin was initially carried out using an acid-soluble collagen extraction methodology developed at the Laboratory of Healing Pharmacology and the determination of the moisture content of the collagen extracted by lyophilization of the samples. Then, formulations without collagen and with collagen at 1% and 3% were developed, and preliminary stability tests were carried out, which included pH measurement, centrifugation (3000 rpm / 30 min) and viscosity tests. After the first day of testing, the samples were divided into three storage environments (refrigerator, at 8ºC; room temperature, 25ºC and oven, 40ºC). The entire stability test lasted 14 days. Data were analyzed by analysis of variance (ANOVA), followed by Tukey's post-test for multiple comparisons. The average moisture content (94.76%), yield (30.74%) and standard deviation (2.23% in relation to moisture and 4.27% in relation to extraction yield) showed that the methodology is reproducible and guarantees the extraction of large amounts of collagen. Among the formulations tested, hydrogel base 3 and formulations 4 (1% collagen) and 5 (3% collagen) showed the best results in the preliminary stability tests, regarding organoleptic properties, appearance, homogeneity, pH and viscosity. All these considerations were decisive for choosing the best hydrogel formulation for the new collagen-based product for tilapia skin, because in addition to being stable under refrigeration, the product base easily incorporates collagen, at the two concentrations proposed for the study, 1% and 3%, making it possible to carry out future hydrogel characterization studies, accelerated and long-term stability studies and the evaluation of the promising potential for wound healing.